The Impact of Per Capita Income and Labour Absorption toward Poverty Level in Gorontalo Province - Nelvi Oktaviani R Gobel; Sri Endang Saleh (Gorontalo State University, 2020)
This research aims to investigate the impact of per capita income and labour absorption toward poverty level in Gorontalo Province during 2012-2017. This research uses time-series data model from secondary datasets that is obtained from Central Statistics Bureau (Badan Pusat Statistik, BPS). Main findings of this research shows that per capita income has negative impact on poverty level in Gorontalo province while labour absorption has positive impact on poverty level in Gorontalo Province. Keywords: Poverty; Per Capita Income; Labor Absorption